Advancing child health through safe hydration - Sunardi, Diana (World Nutrition Journal, 2025)
Diarrhea is One in five children in Indonesia does not drink enough water, but that’s not the only problem regarding child health and water consumption. The prevalence of Diarrhea in Indonesian children is one in four children under 5 years old. The high prevalence is closely linked to poor sanitation and unsafe drinking water. Water comprises 75% body weight in infants to 55% in the elderly, and plays very crucial role in cellular hemostasis and life. Therefore, the optimal functioning of our body requires a good hydration level from safe drinking water.